Characterization of keratinocytes, fibroblasts and melanocytes isolated from human skin using gene markers - Wong, Pau-Ring; Nur Fatin Nabilah Mohd Sahardi,; Tan, Jen-Kit; Chua, Kien-Hui; Wan Zurinah Wan Ngah,; Suzana Makpol, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Cells isolated from skin have wide applications in studies of the pathogenesis of skin-related diseases and the construction of 3D skin equivalents. This study aimed to isolate keratinocytes, fibroblasts, and melanocytes from human foreskin and characterize the purity of the cell types. Keratinocytes, fibroblasts, and melanocytes from human foreskin were isolated by differential trypsinization and media selection. The purity of the cell types was characterized based on the expression of gene markers. The assessment of gene marker expression involved RNA extraction, primer design, quantitative polymerase chain reaction (qPCR) and immunocytochemical staining. Our results showed that in cocultures of keratinocytes and fibroblasts isolated from the dermis, fibroblasts could be separated from keratinocytes by quick trypsinization and culture in Dulbecco’s modified Eagle’s medium. The remaining keratinocytes are cultured in Epilife medium. Melanocytes in cocultures of melanocytes and keratinocytes isolated from the epidermis could be selected by changing Epilife medium to M254 medium. Gene marker results suggested that cytokeratin 14 (CK14) is a suitable marker for keratinocytes, elastin (ELN) is a suitable marker for fibroblasts, and tyrosinase (TYR) and tyrosinase-related proteins 1 and 2 (TYRP1 and TYRP2) are suitable markers for melanocytes. In conclusion, keratinocytes, fibroblasts, and melanocytes can be isolated from the same human foreskin sample by differential trypsinization and media selection techniques and characterized by suitable gene markers. This finding will aid in the isolation of pure skin cell types for various applications in regenerative medicine and toxicity studies.